2012
DOI: 10.5586/aa.2012.016
|View full text |Cite
|
Sign up to set email alerts
|

Biological determinants of plant and crop productivity of flax (Linum usitatissimum L.)

Abstract: A b s t r a c tIn Poland the cultivation of the fibrous form of flax (Linum usitatissimum L.) is dying out, but the acreage of its oilseed form, linseed, which provides seed (Semen lini) used in therapy and being a source of -linolenic acid, is expanding. Nowadays, linseed is grown in 64 countries of the world, but yield levels in these countries vary greatly. Under European conditions, seed yield of linseed shows high variation, which is evidence of little knowledge of the biology of this plant and the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 21 publications
0
15
1
1
Order By: Relevance
“…However, TSW was characterized by a more complex determinism with respect to SEED_Y, as it responded to a higher number of factors, which may have raised variability, weakening the correlation between SEED_Y and TSW. The current results, therefore, do not confirm the validity of TSW and BPP as selection criteria for yield, as reported by other authors (Adugna & Labuschagne 2003; Diederichsen & Raney 2006; Zając et al 2012).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, TSW was characterized by a more complex determinism with respect to SEED_Y, as it responded to a higher number of factors, which may have raised variability, weakening the correlation between SEED_Y and TSW. The current results, therefore, do not confirm the validity of TSW and BPP as selection criteria for yield, as reported by other authors (Adugna & Labuschagne 2003; Diederichsen & Raney 2006; Zając et al 2012).…”
Section: Discussioncontrasting
confidence: 90%
“…Cultivar evaluation should also adequately characterize the response to climatic factors, which can play a major role in the success of cultivation (D'Antuono & Rossini 1995; Zając et al . 2012). Field-based research conducted over the last two decades has demonstrated that linseed yield is strongly affected by environmental factors, causing high inter-annual yield variations (Cremaschi et al 1995; Casa et al 1999; Hassan & Leitch 2001; Adugna & Labuschagne 2002, 2003; Zając et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster contained accessions originating from different geographical regions, indicative of a weak relationship between trait performance and geographical origins [32]. There is consensus that linseed yields and the biochemical quality of their seeds vary greatly across the universe and are strongly influenced by climatic conditions [33].…”
Section: Discussionmentioning
confidence: 99%
“…In trials conducted in France only half of the sown seeds germinated (Flenet et al 2006). According to Zając et al (2012) the highest yield of linseed was achieved when 400 to 600 seeds per 1 m 2 were sown.…”
Section: Plant Densitymentioning
confidence: 96%